The avant-garde searches in the national historical and literary process of 1960- 1980-s - Rosalia M. Svetlova3Venera R. Amineva1 Leysan G. Ibragimova2 (Opción, 2019)
The aim of the study is to investigate the avant-garde searches in the national historical and literary process of 1960-1980-s via the system-structural, comparative-typological and comparative research methods. As a result, the second direction of avant-garde searches is connected with the use of different-stage figurative languages (mythopoetic, troped, simple word) within the same work, which enters into dialogue with each other. It is concluded that the avantgarde searches of Yuzeev, R. Akhmetzyanov reflect the general patterns of the national historical and literary process and at the same time are associated with the processes of national-cultural selfidentification of individual author’s artistic systems.